2018
DOI: 10.1038/s41598-018-36342-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles alteration after infection of virus, bacteria, and parasite in the Olive flounder (Paralichthys olivaceus)

Abstract: Olive flounder (Paralichthys olivaceus) is one of economically valuable fish species in the East Asia. In comparison with its economic importance, available genomic information of the olive flounder is very limited. The mass mortality caused by variety of pathogens (virus, bacteria and parasites) is main problem in aquaculture industry, including in olive flounder culture. In this study, we carried out transcriptome analysis using the olive flounder gill tissues after infection of three types of pathogens (Vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Viruses have also been shown to alter the levels of various ECM proteins in multiple cell types [54–56]. Our data revealed a significant reduction in proteins involved in cell adhesion, focal adhesion, cell migration and ECM organization in infected cells.…”
Section: Discussionmentioning
confidence: 55%
“…Viruses have also been shown to alter the levels of various ECM proteins in multiple cell types [54–56]. Our data revealed a significant reduction in proteins involved in cell adhesion, focal adhesion, cell migration and ECM organization in infected cells.…”
Section: Discussionmentioning
confidence: 55%
“…Most importantly, we also found that signaling related to immune response, Fcepsilon receptor signaling pathway, viral process, and symbiosis, encompassing mutualism through parasitism signaling affected by the COVID-19 targeting human cellular miRNAs (Table.6). The signaling mentioned above is important to fight against viral infections [45][46][47][48]. Both KEGG and GO pathway analysis revealed that COVID-19 targeting human cellular miRNAs are involved in the number of age-related complications.…”
Section: And Supplementarymentioning
confidence: 99%
“…The two most significant aquaculture species in East Asia, including South Korea, Japan, and China, are olive flounder (Paralichths olivaceus) and black rockfish (Sebastes schleglii), also known as Korean rockfish [17][18][19][20]. The production of olive flounder was 41,800 tons, while the output of black rockfish was 17,500 tons in 2021, according to the Korean Statistical Information Service data [21].…”
Section: Introductionmentioning
confidence: 99%